Predictors of stress in patients with Lupus - Jolly, Meenakshi; Katz, Patricia (Frontiers in Medicine, 2022)
Background: Stress is common in patients with Systemic Lupus Erythematosus (SLE), and is associated with depression, fatigue, and disease flares. Stress may be modifiable and identifying those at high risk allows clinicians and allied health care professionals to develop a multidisciplinary management plan to direct appropriate resources. This study aimed at identifying predictors of high stress over time among patients with SLE. Methods: Longitudinal data from two interviews of the Lupus Outcomes Study two years apart from 726 patients with SLE were analyzed for stress, measured using the Perceived Stress Scale (PSS; high-stress PSS ≥6). T-test and Chi-square analyses compared patient characteristics by high-stress status. Logistic regression were conducted with High stress as the dependent variable. Covariates included demographics, disease features, quality of life (QOL), health care utilization (HCU), and comorbidities. QoL was measured using the SF-36 form (Physical Component Score, PCS; Mental Component Score, MCS) and MOS Cognitive Functioning Scale (CFS). HCU indicated having established care with a Rheumatologist, emergency room or hospitalization use, and quality of care. P-values ≤ 0.05 were considered significant. Results: Mean age of the cohort was 50.6 (12.5) years, 92% were women and 70% were Caucasian. Mean (SD) PSS was 5.3 (3.6), and high stress (PSS >6) was noted in 253 participants. Those with high stress were more frequently women, below the poverty line, and less commonly employed. They had a greater prevalence of comorbidities and HCU; and worse disease severity (activity, flare, damage) and QOL. On regression analyses, high stress (baseline) was associated with younger age, married status, worse QOL, and presence of diabetes. Better QOL (PCS, MCS) independently predicted decreased odds of high stress, while high stress (baseline) predicted high stress (OR 3.16, 95% CI 1.85,5.37, p 0.0007) at follow-up, after adjusting for demographics, disease features, HCU, and comorbidities. Conclusions: Patients with SLE should be routinely screened for QOL and Stress during their clinical care, to identify those at risk for poor health outcomes. This information can facilitate multidisciplinary management for those at risk for worse health outcomes.